Brick Masonry Components Exposed to Aggressive Environment: Mechanical Behavior and Properties - An Experimental Investigation - Roopanjali.S,; P.Nanjundaswamy,; K.Manjunath.,; Raghuprasad P.S, (International Journal of Engineering and Management Research, 2022)
Deterioration of porous materials lead to severe damage in buildings. Salt weathering being the most common deterioration mechanism in porous materials which is related with the growth of crystal and pressure inside the pores of the materials associated with masonry. However the study on effect of salts on behavior of masonry as a whole unit and their individual components have not been elucidated for Indian conditions and only limited knowledge is available on deterioration of mortars which is the binder of brick masonry. This paper presents primary investigational study on components of masonry made of burnt clay bricks and cement mortar at joints in order to assess the damage induced by salts (sulphate and chloride). With this as aim, specimens were prepared in laboratory and were subjected to accelerated weathering conditions of different durations in sodium chloride and magnesium sulphate solutions which are the most common salts of attack in brick masonries when the environmental ambiance is strongly aggressive, either acidic or alkaline or in presence of sulphate and chloride produces physicochemical external attack and alterations in their integrity. Relevant studies have also been performed in the field by other authors, but in the study, conventional mortar mixes are manufactured and their behavior in aggressive environments. Certain mortar properties related to their behavior such as density, compressive strength, water absorption and porosity are analyzed for their disruptive effects. The paper presents the results obtained by the exposure of brick masonry and its components for a total duration of 14 weeks exposed to aggressive environment. Variation in mechanical properties of brick and its components were observed as the concentration of salts increased in the simulated environment created artificially in laboratory.